Variability of some qualitative forage characteristics in Italian Lucerne ecotypes under different cutting schedules - U. Ziliotto; S. Macolino; M. Scotton (Italian Journal of Animal Science, 2011)
Quantitative characteristics of yield of Lucerne (Medicago sativa L.) rotate meadows could be affect by various factors, of which the most important are: environment of meadow location, fertilization (amount and kind of nutrients), irrigation, climatic conditions, harvest period, vegetative stage and also the cultivar used (Parrini e Bonari, 2002).With the aim to contribute to define the effect of the last factor mentioned on the qualitative characteristics of the Lucerne yield, a plot trial was carried out for two years where 15 cultivars of Lucerne and.......